Implementasi ramah lingkungan di pusat kuliner pasar Kreneng Denpasar, Bali - Susanto, Budi; Paramita, Ratri; Zulfan, Muhammad; Sutiarso, M. Agus (Yayasan Mitra Persada Nusantara, 2024)
This research aims to find out how the environmentally friendly concept is implemented and what must be improved to raise the awareness of eco-friendly behavior of the food stall runners at the culinary center of Kreneng night market in Denpasar. Environmentally friendly behavior or eco-friendly behavior refers to behavior that is not harmful to the environment. In terms of products, this means everything from production to packaging and marketing must be environmentally safe. Business activities that are not environmentally friendly can cause global warming. Furthermore, global warming means increasing the average temperature of the earth's atmosphere, sea, and land. The impact of global warming results in sea level rise, climate change, damage to organisms, and effects on water availability. The impact of environmental damage will chain if there is no effort to anticipate it. One way to anticipate ecosystem damage that needs to be done is implementing environmentally friendly behavior. An environmentally friendly lifestyle needs to be implemented in order to minimize damage to the ecosystem. Environmentally friendly business activities are currently being promoted throughout the world. Ecosystem damage affects economic, social problems, and even socio-political stability in a country and even the world and will have a direct or indirect impact on human life. This research is descriptive qualitative research. Data sources were obtained from library studies and direct interviews with business actors in the restaurant sector. From this research, it was found that several large restaurants, especially those located in 5-star hotel environments, have carried out business activities that indicate they are environmentally friendly by carrying out green actions, green food, and green donations.